Technique 29: Deviance, Moral Indignation, and Public Policy - Huff, C. (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Teaching Objectives/Student Learning Outcomes: To illustrate for students (1) the subjective nature of our personal perceptions and assessments of "deviant" acts and their comparative seriousness; (2) the normative violations that evoke the strongest and weakest negative reactions and preferred sanctions; (3) those acts that appear to be situated at the boundaries of what is considered to be "deviant"; and (4) that cultural lags may exist between public perceptions of deviance and official public policy concerning appropriate sanctions for various "deviant" behaviors. The personal experience provided by this teaching technique helps students learn that perceptions of various types of "deviance" and the degree of moral indignation associated with these perceptions directly influence the severity of punitiveness that we prescribe for such "deviant" behaviors. They also tend to reach strong consensus concerning those acts that elicit the most and the least moral indignation. Finally, through classroom discussion, they learn that while law generally reflects this consensus, there are areas where legal sanctions may lag behind contemporary public perceptions of the seriousness of certain "deviant" acts.